2021
DOI: 10.1101/2021.02.10.430603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An angiospermNLRatlas reveals thatNLRgene reduction is associated with ecological specialization and signal transduction component deletion

Abstract: Nucleotide-binding site-leucine-rich repeat receptor (NLR) genes comprise the largest family of plant disease resistance genes. NLR genes are phylogenetically divided into the TNL, CNL, and RNL subclasses. NLR copy numbers and subclass composition vary tremendously across angiosperm genomes. However, the evolutionary associations between genomic NLR content and plant lifestyle, or between NLR content and signal transduction components, are poorly characterized due to limited genome availability. Here, we estab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 68 publications
5
21
0
Order By: Relevance
“…The remaining two A. thaliana RNL genes form a sister lineage to ADR1, corresponding to the NRG1 lineage. This topology is in accordance with the previous finding that the RNL-NRG1 lineage was lost in the common ancestor of monocots (Collier et al, 2011;Shao et al, 2016;Liu et al, 2021).…”
Section: Species-specific Preservation and Amplification Of Ancestral Nlr Lineages During The Speciation Of Barley And Wheatsupporting
confidence: 93%
See 4 more Smart Citations
“…The remaining two A. thaliana RNL genes form a sister lineage to ADR1, corresponding to the NRG1 lineage. This topology is in accordance with the previous finding that the RNL-NRG1 lineage was lost in the common ancestor of monocots (Collier et al, 2011;Shao et al, 2016;Liu et al, 2021).…”
Section: Species-specific Preservation and Amplification Of Ancestral Nlr Lineages During The Speciation Of Barley And Wheatsupporting
confidence: 93%
“…The results showed that the 468 barley NLR genes comprise one RNL and 467 CNL genes. TNL genes were not detected in the barley genome, which is consistent with the notion that TNL genes are lost in the common ancestor of monocots (Collier et al, 2011;Shao et al, 2016;Liu et al, 2021).…”
Section: Barley Genome Contains Over 400 Nlr Genessupporting
confidence: 86%
See 3 more Smart Citations